2007
DOI: 10.1002/bem.20325
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of pregnant dairy heifer to magnetic fields at 60 Hz and 30 µT

Abstract: Thirty-two pregnant Holstein heifers weighing 499 +/- 45 kg, at 3.1 +/- .7 months of gestation and 21 +/- 2.0 months of age were confined and exposed to 30 microT magnetic fields (MFs) and a 12 h light/12 h dark light cycle. The heifers were divided into two replicates of 16 animals. Each replicate was divided into two groups of eight animals each, one group the non-exposed and the second, the exposed group. The animals were subjected to the different treatments for 4 weeks. After 4 weeks, the animals switched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
1
4
1
Order By: Relevance
“…Our results agree with previous findings that short-term powerfrequency magnetic field exposure causes an increase in the body mass of mice and cattle [1][2][3][4]18]. Electrical fields alone did not produce any change in the body mass of pregnant lactating cows relative to unexposed controls [19], whereas magnetic fields did [2].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with previous findings that short-term powerfrequency magnetic field exposure causes an increase in the body mass of mice and cattle [1][2][3][4]18]. Electrical fields alone did not produce any change in the body mass of pregnant lactating cows relative to unexposed controls [19], whereas magnetic fields did [2].…”
Section: Discussionsupporting
confidence: 92%
“…There is some evidence that exposure of various animals, including mice and cattle, to a power-frequency magnetic field can increase body mass relative to unexposed controls [1][2][3][4]. This is a potentially interesting finding because the strength of the Earth's magnetic fields varies depending on latitude, and has varied over evolutionary time.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of Burchard et al (2004) did not confirm these results in which IGF-1 levels on pregnant dairy heifers exposed to 10 kV/M 60 Hz EF could not been detected significantly different than shamexposed groups. Nevertheless, in their recent study, slight decrease in concentration of IGF-1 of pregnant dairy heifer was reported with 60 Hz and 30 mT EMF exposures (Burchard et al, 2007). IGF-1 levels were found significantly lower in prenatal exposure group than the post-natal and sham-exposed groups in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…The exposure of dairy cattle to a vertical electric field of 10 kV/m and a uniform horizontal magnetic field of 30  μ T for 28 days did not change the nocturnal blood melatonin level [86]. Similarly, no changes in melatonin secretion were observed in other experiments performed on dairy cows [87, 88] and on lambs [89, 90]. The studies of American kestrels reveled that a long-term exposure to electromagnetic fields (60 Hz, 30  μ T, 10 kV · m −1 ) caused changes in melatonin secretion [91].…”
Section: Effects Of Electric Magnetic and Electromagnetic Fieldsmentioning
confidence: 99%